A knock-in mutation at cysteine 144 of TRIM72 is cardioprotective and reduces myocardial TRIM72 release. (November 2019) - Fillmore, Natasha; Casin, Kevin M.; Sinha, Prithvi; Sun, Junhui; Ma, Hanley; Boylston, Jennifer; Noguchi, Audrey; Liu, Chengyu; Wang, Nadan; Zhou, Guangshuo; Kohr, Mark J.; Murphy, Elizabeth
Abstract: TRIM72 is a membrane repair protein that protects against ischemia reperfusion (I/R) injury. We previously identified Cys 144 (C144) on TRIM72 as a site of S-nitrosylation. To study the importance of C144, we generated a knock-in mouse with C144 mutated to a serine (TRIM72 C144S). We subjected ex vivo perfused mouse hearts to 20 min of ischemia followed by 90 min of reperfusion and observed less injury in TRIM72 C144S compared to WT hearts. Infarct size was smaller (54 vs 27% infarct size) and cardiac functional recovery (37 vs 62% RPP) was higher for the TRIM72 C144S mouse hearts. We also demonstrated that TRIM72 C144S hearts were protected against I/R injury using an in vivo LAD occlusion model. As TRIM72 has been reported to be released from muscle we tested whether C144 is involved in TRIM72 release. After I/R there was significantly less TRIM72 in the perfusate normalized to total released protein from the TRIM72 C144S compared to WT hearts, suggesting that C144 of TRIM72 regulates myocardial TRIM72 release during I/R injury. In addition to TRIM72's protective role in I/R injury, TRIM72 has also been implicated in cardiac hypertrophy and insulin resistance, and secreted TRIM72 has recently been shown to impair insulin sensitivity. However, insulin sensitivity (measured by glucose and insulin tolerance) of TRIM72 C144S mice was not impaired. Further, whole body metabolism, as measured using metabolic cages, was not different in WT vs TRIM72 C144S mice and we did not observe enhanced cardiac hypertrophy in the TRIM72 C144S mice. In agreement, protein levels of the TRIM72 ubiquitination targets insulin receptor β, IRS1, and focal adhesion kinase were similar between WT and TRIM72 C144S hearts. Overall, these data indicate that mutation of TRIM72 C144 is protective during I/R and reduces myocardial TRIM72 release without impairing insulin sensitivity or enhancing the development of hypertrophy. Highlights: TRIM72 is a membrane repair protein that protects against I/R injury. We generated a TRIM72 knock-in mouse with C144 mutated to a serine. TRIM72 C144S hearts were protected against ex vivo and in vivo models of I/R injury. TRIM72 C144S hearts showed no changes insulin sensitivity or cardiac hypertrophy.